Sosialisasi Pencatatan Perkawinan Untuk Menjamin Keabsahan dan Perlindungan Hukum di Majlis Ta'lim Miftahul Istiqomah, Desa Taringgul Landeuh, Kecamatan Kiarapedes, Kabupaten Purwakarta - Silpa, Dawian; Prasetiadi, Yan Septiana; Annisa, Akke Azhar; Gussevi, Sofia (Yayasan Cendekia Gagayunan Indonesia, 2025)
Marriage registration is an important aspect of marriage law in Indonesia which has implications for the validity and legal protection of married couples. Indonesia has various marriage legal systems, both customary and religious, which are regulated in Law no. 1 of 1974. In Islam, marriage registration is not a pillar of marriage, but has significance in providing legal certainty. Without registration, the marriage loses legal force, potentially causing problems in the future. This research uses the Participatory Research method by involving the community in socializing marriage registration in Taringgul Landeuh Village, Kiarapedes District, Purwakarta Regency. This activity goes through the stages of observation, preparation, implementation and evaluation. The results of the activity show that there are still people who marry without official registration, which has an impact on legal protection for partners and their offspring. This socialization succeeded in increasing public awareness about the importance of registering marriages as a means of complying with the law and guaranteeing the validity of marriages in the eyes of the state